Type 2 Diabetes Mellitus and the Association of Candidate Genes in Asian Indian Population from Hyderabad, India - Khan, Imran Ali (Journal of clinical and diagnostic research, 2015)
Genetic and environmental factors play an important role in susceptibility to type 2 diabetes mellitus (T2DM). Several genes have been implicated in the development of T2DM. Genetic variants of candidate genes are, therefore, prime targets for molecular analysis. In this study, we have selected 3 candidate genes, namely, TCF7L2, SLC30A8, and IGF2, for assessing their association with T2DM in an Indian population. Five hundred individuals were enrolled in this case-control study- 250 T2DM patients and 250 healthy control individuals. Clinical characteristics were obtained for all subjects, and genotype analysis was performed by PCR-RFLP analysis. Allele and genotyping frequencies, odds ratios, and 95% confidence intervals were calculated for 3 single nucleotide polymorphisms (SNPs), 1 each from TCF7L2 (rs7903146), SLC30A8 (rs13266634), and IGF2 (rs680) in T2DM patients. The rs7903146 and rs680 polymorphisms were found to be significantly associated with T2DM (p < 0.05), whereas the rs13266634 polymorphism was not (p > 0.05). The multifactor dimensionality reduction method identified the particular polymorphisms associated with an increased risk of disease. The present study indicated that the gene-gene interaction model successfully predicted T2DM risk based on TCF7L2 and SLC30A8 polymorphisms. These results provide strong evidence of independent association between T2DM and the 3 SNPs analysed herein.